MUTU PENDIDIK DAN TENAGA KEPENDIDIKAN DI MI AL HIKMAH ARGO MULYO KECAMATAN MUARA SUGIHAN KABUPATEN BANYUASIN - Rahmat, Rahmat; Asrori, Achmad; Murtafiah, Nurul Hidayati; Irawan, M. Nur Lukman (UNISAN JURNAL, 2023)
The low quality of education is a problem that is evenly experienced by every educational institution. In order to achieve quality education, it is necessary to make efforts to improve the quality of education in order to achieve quality education. Educators and educational staff are the most important spearheads in the progress of an educational institution. On this basis, it is necessary to improve the standard quality of educators and educational staff. Educational institutions must be able to provide good service and quality in order to be able to compete with other educational institutions. This research has the following objectives: 1) To find out the quality of educators and education staff, how to improve the quality of educators and education staff at MI Al Hikmah Argo Mulyo, Muara District Sugihan Banyuasin This type of research is qualitative using data collection techniques, namely data triangulation. The data obtained were analyzed descriptively by means of data reduction, data presentation and conclusion. The results of this study indicate that the improvement in the standard quality of educators and educational staff follows the Phlip B Crosby model, namely conformance requirements, namely quality in accordance with what is standardized, according to the National Education Standards. After knowing the quality in madrasas, then the efforts of the head of the madrasa to improve the quality of educators and educational staff through programs created, namely through MGMP, IHT. In addition to these efforts, the head of the madrasa also motivates teachers and evaluates their performance.